Recent Progress on the Applications of Carbonaceous and Metal-Organic Framework Nanomaterials for Supercapacitors - Zheng, Sheng Qiang; Lim, Siew Shee; Foo, Chuan Yi; Haw, Choon Yian; Chiu, Wee Siong; Chia, Chin Hua; Khiew, Poi Sim (Frontiers in Materials, 2021)
Supercapacitors (SCs) have been widely investigated in the realm of energy resulting from their superior long lifespan and remarkable power density. However, their practical usage is limited because of the high effective resistance and relatively low energy density. Electrode material is crucial for determining the performance of SCs, so the innovation and development of advanced electrode materials is particularly important. Metal-organic frameworks (MOFs) and carbonaceous materials, including MOF-derived carbons and carbon nanotubes (CNTs), are befitting as electrode active materials for SCs on the strength of the unique features of high porosity, tunable structures and easy formation of composites with other compounds. Hence, great efforts were devoted on the synthesis strategies and structural modifications of electrodes to enhance the performance of SCs. In this review, the recent innovations in the realm of SCs, including the application of pristine and derivatives of MOFs as SC electrode materials were extensively studied. Furthermore, the functions and electrochemical performance of various MOFs and their derivatives (e.g., MOF-derived carbons) were analyzed accordingly. Lastly, the innovations and application of CNTs as SC electrode active materials are systematically summarized. This review highlights the electrochemical performance of some advanced MOF- and carbon-based materials, and the critical factors for SC electrode active materials to achieve excellent electrochemical performance in the application of energy storage systems.